Improving the quality of education at drawing lessons with the usage of information technologies - Xaitov, Javoxir (Рroblems of engineering and professional education, 2022)
The article deals with information technologies for the education system. As a result, the country’s education system is moving to new educational technologies based on modern information technologies. Thanks to modern information technology, multimedia, the transition to other languages and letters of the alphabet, the Internet, web technologies, electronic virtual libraries, distance learning and other technologies, technology is provided. This, in turn, requires teachers today not only to be in the field, but also to teach young people, and teaching requires modern equipment and the acquisition of certain knowledge and information. The relevance is also considered the problem of learning in the field of communication technologies, improving the quality of education, expanding the mental abilities of students, enhancing the development of independent work of students. As a result, the scientific research process can lead to a variety of methodological approaches.